Meningkatkan Imunitas Keluarga Melalui Penanaman Toga (Tanaman Obat Keluarga) - Septriani Septriani; Purmini (Kreativasi : Journal of Community Empowerment, 2022)
The Covid-19 case has major impact on Indonesia people, especially on health and economy. Increasing in Covid-19 cases in Bengkulu shows that prevention of Covid-19 is still not optimal. Family medicinal plants (toga) can be an alternative treatment to prevent the spread of Covid-19. This is because toga can increase the body's immunity such as consumption of herbs, herbal medicines and others. However, cultivation and efforts to provide toga in Bengkulu have not been maximized. The purpose of this service activity is to encourage public awareness to develop household toga cultivation as an immunity drug to prevent the spread of Covid-19. The results show that the community is aware of the importance of planting toga in the household environment.